Orient and Occident Encounters in Dimitrije Buzarovski’s Oratorio “Radomir’s Psalms” - Jordanoska, Trena (University of Ljubljana, 2015)
The oratorio Radomir’s Psalms op. 47 (1999) by Dimitrije Buzarovski addresses Orthodox chant in a Western tradition, embedding Eastern modal monodic sacred and folk tradition into Western polyphonic sacred and secular tonal forms. The work is also an example of the influence of the cultural environment upon shaping of the musical ideas.
Srečanja med Vzhodom in Zahodom v oratoriju »Radomirjevi psalmi« Dimitrija Buzarovskega
Keywords: Dimitrije Buzarovski, Radomir’s Psalms, oratorio, Orthodox chant